The conciliation of aesthetics and ethics in contemporary animalist art - GUTIÉRREZ-JORDANO, Carmen (Utopía y Praxis Latinoamericana, 2025)
This article addresses the problem of the relationship between aesthetics and ethics in animalist art. The starting point is the affirmation of art as a suitable field to deal with the maltreatment and cruelty that animals receive from human beings. The animals are used by an art without animalistic intention and with symbolic pretensions, or by a properly animalistic art. The main ethical problem that arises concerns animalistic art, which, with the intention of ethically defending animals, treats them cruelly. The method of the work is the hermeneutic interpretation of texts and works of art. The objective is to clarify the problem of the reconciliation of the aesthetic and the ethical in current animalistic art. It is concluded that the solution to the problem of the relationship between aesthetics and ethics lies in the fact that the aesthetic is something internal to the ethical.